2011
DOI: 10.1007/s10803-011-1284-z
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Behavioral Interventions for Repetitive Behaviors in Autism

Abstract: Restricted and repetitive behaviors (RRBs) are a core symptom of autism spectrum disorders (ASD). There has been an increased research emphasis on repetitive behaviors; however, this research primarily has focused on phenomenology and mechanisms. Thus, the knowledge base on interventions is lagging behind other areas of research. The literature suggests there are evidence-based practices to treat “lower order” RRBs in ASD (e.g., stereotypies); yet, there is a lack of a focused program of intervention research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
143
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(151 citation statements)
references
References 126 publications
2
143
0
3
Order By: Relevance
“…At this stage, a further 27 studies were excluded from the final review of data for the following reasons. Eight studies were reports of secondary data (Boyd et al 2012;King and Desaulnier 2011;Lang et al 2010;Langdon et al 2013;Reaven 2009, 2011, Reaven et al 2009Rotheram-Fuller and MacMullen 2011;Scattone and Mong 2013), one study (Sze and Wood 2008) was a duplicate that had not been previously filtered out, one (White et al 2013) reported a non-significant effect of the intervention, five studies reported the effects of CBT for core features of ASD rather than mental health symptoms (Drahota et al 2011;Kenworthy et al 2014;Scarpa and Reyes 2011;Wood et al 2009aWood et al , b, 2014 and 12 included (n = 1) designs (Cook et al 1993;Lehmkuhl et al 2008;Nadeau et al 2014;Reaven and Hepburn 2003;Schleismann and Gillis 2011;Wood 2007, 2008) or did not have a comparator group (Reaven et al 2012b;Ooi et al 2008;Ozsivadjian and Knott 2011;White et al 2010;White et al 2009). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At this stage, a further 27 studies were excluded from the final review of data for the following reasons. Eight studies were reports of secondary data (Boyd et al 2012;King and Desaulnier 2011;Lang et al 2010;Langdon et al 2013;Reaven 2009, 2011, Reaven et al 2009Rotheram-Fuller and MacMullen 2011;Scattone and Mong 2013), one study (Sze and Wood 2008) was a duplicate that had not been previously filtered out, one (White et al 2013) reported a non-significant effect of the intervention, five studies reported the effects of CBT for core features of ASD rather than mental health symptoms (Drahota et al 2011;Kenworthy et al 2014;Scarpa and Reyes 2011;Wood et al 2009aWood et al , b, 2014 and 12 included (n = 1) designs (Cook et al 1993;Lehmkuhl et al 2008;Nadeau et al 2014;Reaven and Hepburn 2003;Schleismann and Gillis 2011;Wood 2007, 2008) or did not have a comparator group (Reaven et al 2012b;Ooi et al 2008;Ozsivadjian and Knott 2011;White et al 2010;White et al 2009). …”
Section: Resultsmentioning
confidence: 99%
“…Research would seem to suggest that the underlying cognitive mechanisms and manifestation of OCD, depression and even PTSD are the same in typically developing young people and those with ASD (e.g. Barnhill and Smith Myles 2001;Boyd et al 2012;Cook et al 1993;Ghaziuddin et al 2002;Hedley and Young 2006;Howlin and Clemments 1995;Mehtar and Mukaddes 2011;Whitehouse et al 2009). This suggests that interventions should be tailored to directly target these symptoms and/or disorder-specific manuals should be adapted to treat each separate disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Summaries were presented with an aim toward providing clinicians with some options to consider in structuring treatment for problems related to cooperating with transitions across activities. The authors also recommend the following review papers that have each highlighted unique emphases relative to transition support considerations including Lequia et al (2012) and Koyama and Wang (2011) [reviewing research on activity schedules]; Sterling-Turner and Jordan (2007) [with special focus on applications for classroom and student supports]; and Boyd et al (2012) [which addressed intervention strategies with differentiation between Blower^and Bhigher^order repetitive behaviors]. The body of literature taken together does suggest there are a number of treatment options that can be used to directly target difficulty with transitions.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most widely used evidence-based interventions for alleviating problem behaviour in children with ASD is behavioural interventions based on operant conditioning principles (Boyd, McDonough, & Bodfish, 2011;Bregman, Zager, & Gerdtz, 2005;Campbell, 2003;Green et al, 2006;Horner et al, 2002;Myers & Johnson, 2007). In particular, within the range of these interventions that aim to reduce problem behaviour, there appears to be a shift from child-focused behavioural interventions, which are typically carried out by trained therapists to focus exclusively on teaching the target child (e.g., early intensive behavioural intervention [EIBI] programmes), towards an increasing recognition of parent-focused behavioural interventions, which are provided to train parents in the use of appropriate behavioural strategies with their child (e.g., the Stepping Stones Triple P [SSTP] programme) (e.g., Birkin, Anderson, Moore, & Seymour, 2004;Brookman-Frazee, Stahmer, BakerEriczén, & Tsai, 2006;Brookman-Frazee, Vismara, Drahota, Stahmer, & Openden, 2009;Francis, 2005;Matson, Mahan, & Matson, 2009;Schreibman, 2000;Schreibman & Anderson, 2001).…”
Section: Problem Behaviour In Children With Autism Spectrum Disordersmentioning
confidence: 99%